Research on agricultural science and technology advancement enabling the development of rural industrial incorporation from the perspective of decomposition - Sheng Yao; Guosong Wu (Agricultural Economics (AGRICECON), 2025)
Taking China as an example in this study, we aim to reveal the enabling effects of agricultural science and technology advancement on the progress of rural industrial incorporation at a relatively more refined level. The main innovation in this study lies in the decomposition of agricultural science and technology advancement, followed by an analysis of its effect on rural industrial incorporation along both linear and non-linear dimensions. The study results show that, along the linear dimension, agricultural science and technology advancement, agricultural knowledge advancement and agricultural technology advancement play significant driving roles in the progress of rural industrial incorporation. However, although the estimated coefficient of the integration of agricultural knowledge advancement and technology advancement is positive, it is not statistically significant. Along the non-linear dimension, agricultural science and technology advancement, agricultural knowledge advancement and agricultural technology advancement all exhibit significantly positive effects across different intervals. However, although the integration of agricultural knowledge advancement and technology advancement also shows a positive effect, its significance appears only in the second interval, indicating that the effect of this variable in promoting rural industrial incorporation can be realised only under certain conditions